INVESTIGATING ENGLISH TEACHERS' BELIEFS ABOUT AND ATTITUDES TOWARDS STUDENTS' NEEDS : a case study at one of the vocational schools in bandung - Wijaya, Ginanjar Putu (2017)
This is a qualitative case study research aiming to find out: 1) English teachers' beliefs about and attitudes towards students' needs, and 2) factors influencing those beliefs and attitudes. The participants were three senior teachers and one substitute teacher at a vocational school in Bandung, Indonesia. The data were collected using questionnaires and semi-structured interviews. It is revealed that the teachers have generally similar beliefs about the importance of English and the most important needs for students. However, they have different approaches to defining, identifying, and making practical decisions about students' needs. There are also apparent differences in attitudes towards students' needs between the senior teachers and the temporary teacher. As for the factors, internal factors such as experiences and observation are the main factors that shape the English teachers' beliefs and attitudes, while the external factors such the 2013 curriculum does indeed have the impacts on the teachers' decisions on teaching, but not necessarily on their prior beliefs. These findings imply that age and experiences may not necessarily lead to teachers from different age or experiences having different beliefs as well, as the investigated teachers have shown that they basically share mostly similar beliefs on multiple topics of students' needs. However, age and experiences may lead to differences in making decisions, attitudes, or behaviors related to students' needs. It is also shown that internal factors such as experiences can be more powerful than external factors in defining teachers' beliefs, but external factors can be more powerful in dictating teachers' actions and decisions, meaning that teachers' beliefs may not always be in the same direction as their attitudes, behaviors, or actions. This can be seen from the differences in pedagogical decisions among the teachers, especially between the senior teachers and the temporary teacher. ;---